2019
DOI: 10.3390/ani9121048
|View full text |Cite
|
Sign up to set email alerts
|

Increased Consumption of Sulfur Amino Acids by Both Sows and Piglets Enhances the Ability of the Progeny to Adverse Effects Induced by Lipopolysaccharide

Abstract: This study determined the effects of increased consumption of sulfur amino acids (SAA), as either DL-Met or Hydroxy-Met (OH-Met), by sows and piglets on their performance and the ability of the progeny to resist a lipopolysaccharide (LPS) challenge. Thirty primiparous sows were fed a diet adequate in SAA (CON) or CON + 25% SAA, either as DL-Met or OH-Met from gestation day 85 to postnatal day 21. At 35 d old, 20 male piglets from each treatment were selected and divided into 2 groups (n = 10/treatment) for a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…At the end of the feeding trial and after 12 h of feed deprivation, 10 male pigs (1 pig/pen) from each treatment were selected according to the treatment average BW for the analysis of the carcass traits and meat quality. The backfat thickness of the pigs was measured 65 mm from the left side of the dorsal midline at the last rib level (P2) by an ultrasound (Renco B-07, Minneapolis, MN, USA), according to Zhang et al (2019) [ 22 ]. The selected pigs were weighed and sacrificed using electrical stunning (120 V, 200 Hz) and exsanguination.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the feeding trial and after 12 h of feed deprivation, 10 male pigs (1 pig/pen) from each treatment were selected according to the treatment average BW for the analysis of the carcass traits and meat quality. The backfat thickness of the pigs was measured 65 mm from the left side of the dorsal midline at the last rib level (P2) by an ultrasound (Renco B-07, Minneapolis, MN, USA), according to Zhang et al (2019) [ 22 ]. The selected pigs were weighed and sacrificed using electrical stunning (120 V, 200 Hz) and exsanguination.…”
Section: Methodsmentioning
confidence: 99%
“…Methionine plays a part in the main functions in the body, including ROS elimination and GSH precursors [ 37 ], and thus methionine is sensitive to oxidative modification [ 38 , 39 , 40 ]. The results of previous investigations pointed out that augmented dietary Met levels exerted antioxidant impacts in poultry.…”
Section: Discussionmentioning
confidence: 99%
“…It is the second or third most limiting amino acid for pigs that are fed corn-soybean meal diets [ 2 , 3 ]; it is used for protein synthesis and is involved in the methylation reactions of DNA and choline metabolism [ 4 , 5 ]. Additionally, methionine acts as the precursor for glutathione and taurine and plays a critical role in antioxidant defense and regulates immune responses in various animal species [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial endotoxin lipopolysaccharide (LPS) can induce inflammation and oxidative stress, which causes damage to different organs and leads to adverse effects on animal productivity [ 10 ]. Our previous study showed that an increased consumption of methionine by both maternal and neonatal pigs can improve the capability of the progeny to cope with the LPS-induced negative effects [ 8 ]. However, the underlining mechanisms in this regard remain unclear.…”
Section: Introductionmentioning
confidence: 99%